The influence of humates produced by “Shubarkol Komir” JSC on the germination of seed material of various vegetable crops - Smagulov, M.K.; Serikbay, A.T.; Alimzhanova, A.Zh.; Ageev, D.V.; Dodonova, A.Sh. (Karagandy University of the name of academician E.A. Buketov, 2024)
The biological activity of humid substances is manifested in increasing the resistance of plants to unfavorable factors and stimulating their metabolic processes, which has a positive effect on the growth characteristics of both seed material and the vegetative part of the whole plant. The article examines the influence of humates produced by “Shubarkol Komir” JSC during pre-sowing soaking on the germination of seed material of various cultivated plants, and assessed their antifungal activity. Commercial humates “Ideal”, “Gumate 7+”, and “Biomaster” humates were used as comparison preparations. In the experiments, seed material of the following crops and varieties was used: tomato, Siberian Yabloko variety; eggplant, Caviar Paradise variety; sweet pepper, D'Artagnan variety; water cress, Abundant-leaved variety; radish, grade “5+”; nut. For tomato and sweet pepper, the best content of humates in the solution for soaking seed material was 0.5%, for eggplant, watercress, radish and chickpeas – 0.1%. The effectiveness and antifungal activity of “Shubarkol Komir” humate is not inferior to commercial drugs used as reference drugs.
«Шұбаркөл көмір» АҚ өндіретін гуматтардың әртүрлі көкөніс дақылдарының тұқымдық материалының өнуіне әсері
Влияние гуматов производства АО «Шубарколь комир» на всхожесть семенного материала различных овощных культур
Keywords: humates; seed material; pre-treatment; germination; germination energy; antifungal activity